2012
DOI: 10.2527/jas.2011-4119
|View full text |Cite
|
Sign up to set email alerts
|

Use of dietary mannanoligosaccharides during rabbit fattening period: Effects on growth performance, feed nutrient digestibility, carcass traits, and meat quality

Abstract: This study was conducted to compare the effects of mannanoligosaccharides (MOS) and antibiotics as a dietary supplement on ADG, ADFI, G:F, and feed nutrient digestibility of rabbits during the fattening period, as well as on carcass traits and meat quality. A total of 512, sixty-day-old hybrid Hyla rabbits were randomly divided into 4 treatment groups based on BW and sex. The 4 treatment groups consisted of a control group and 3 MOS groups. The control group was fed a diet that contained apramycin (50 mg/kg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
1
29
0
3
Order By: Relevance
“…However, reduction of fat percentage is reported in broilers fed a diet containing 3.75 g kg -1 fructooligosaccharide respect to that fed the control diet (Flickinger et al, 2003). Also, studies showed a reduction in fat deposition of the carcass of rabbits fed mannanoligosaccharides (Piccolo et al, 2009;Bovera et al, 2012), in triglycerides of poultry (Bozkurt et al, 2012) and in hepatic lipogenesis and plasma triacylglycerol of humans (Letexier et al, 2003). In the present study, MOS and INU supplementation reduced also mesenteric fat.…”
Section: Discussionmentioning
confidence: 64%
“…However, reduction of fat percentage is reported in broilers fed a diet containing 3.75 g kg -1 fructooligosaccharide respect to that fed the control diet (Flickinger et al, 2003). Also, studies showed a reduction in fat deposition of the carcass of rabbits fed mannanoligosaccharides (Piccolo et al, 2009;Bovera et al, 2012), in triglycerides of poultry (Bozkurt et al, 2012) and in hepatic lipogenesis and plasma triacylglycerol of humans (Letexier et al, 2003). In the present study, MOS and INU supplementation reduced also mesenteric fat.…”
Section: Discussionmentioning
confidence: 64%
“…The raw meat from the left hind leg dissection was ground, freeze-dried and analysed using the following AOAC procedures (1984): moisture (method 950.46), fat (method 930.27) and ash (method 950.153). Protein content, including glucidic molecules and their catabolities (0.25%; Bovera et al, 2012) was calculated by difference.…”
Section: Physical Criteriamentioning
confidence: 99%
“…Fructooligosaccharides and mannan oligosaccharides (MOS) beneficially affect gut health by suppressing enteric pathogens, enhancing immune responses, and improving the integrity of the intestinal mucosa of broilers (Baurhoo et al, 2007). Mannan oligosaccharides can join E. coli and Salmonella and prevents these pathogens from sticking to the intestinal wall (Bovera et al, 2012;Shanmugasundaram et al, 2013). Organic acids are also potential feed additive alternatives to AGP in animal rearing systems (Adil et al, 2011;Sultan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%